First Reported Case of Invasive Cutaneous Penicillium cluniae Infection in a Patient With Acute Myelogenous Leukemia: A Case Report and Literature Review. (23rd May 2021) - Mehta, Devanshi; Hofacker, Samuel A; Villalba, Julian A; Duncan, Lyn M; Branda, John A; Cañete-Gibas, Connie; Wiederhold, Nathan; Moran, Jenna; Fathi, Amir T; Chen, Steven T; Cervantes, Jessica; Hammond, Sarah P
Abstract: Certain Penicillium species are emerging opportunistic pathogens. While these can be common causes of airborne contamination of clinical cultures, an increasing number of reports describe clinically significant disease in the immunocompromised population, particularly in patients with hematologic malignancy. The typical site of infection is respiratory, but disseminated infection is also reported with some frequency. Therefore, culture growth of Penicillium in respiratory and other clinical samples from immunocompromised patients requires thorough investigation with clinical correlation. Here we report a case of angioinvasive Penicillium cluniae infection of the right shin in a patient with acute myeloid leukemia and review reported cases of invasive Penicillium infection (excluding Talaromyces marneffei ) in hematologic malignancy patients to characterize the emerging pathogen in this vulnerable population.